The Urgency of Emotional Intelligence in Higher Education to Improve The Quality of Indonesian Graduates: A Phenomenological Approach - Bobang Noorisnan Pelita; Baby Poernomo; Akhya Ansori; Nico Irawan (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
Currently, social and economic challenges are increasingly felt, raising public awareness of the importance of education. Various employment sectors set a minimum qualification of a bachelor's degree, prompting parents to prioritize their children's education as a preparation for a future career. Education is no longer considered sufficient only up to the high school level, but efforts are made to continue it to higher education. Unfortunately, these fresh graduates only excel academically but have relatively low emotional intelligence. This is a qualitative study with a phenomenological approach. Data collection was conducted through semi-structured interviews with human resources managers who have been responsible for recruiting fresh graduates. To maintain data validity, the researcher conducted source triangulation, by interviewing students who are currently in their fifth semester. The results of this study show that there are still many fresh graduates who are only good academically but still do not understand and have not applied the five aspects of emotional intelligence, namely self-awareness, self-regulation, motivation, empathy, and social skills.